Promoting The Algerian Tourism Sector In Light - Gheffar ,Abdelaziz; Alloti ,Lamine (University of Eloued جامعة الوادي, 2025)
This research explores the current state and prospects of the Algerian tourism sector, emphasizing its potential as a strategic alternative for economic diversification. By analyzing material and human resources, cultural and natural assets, and institutional barriers, the paper sheds light on challenges and opportunities that shape the sector. Special attention is devoted to the National Tourism Development Plan 2030 (SDAT 2030), which was launched to strengthen Algeria’s international competitiveness. The findings suggest that while Algeria has significant tourism resources, success depends on upgrading infrastructure, modernizing governance, and adopting digital promotion strategies. Recommendations focus on improving coordination, investment incentives, and workforce development to make tourism a sustainable contributor to economic growth.
Promoting the Algerian tourism sector in light of the National Tourism Development Plan 2030
مقال
Keywords: Tourism sector; National Development Plan; Tourism Development.